(untitled) (Journal of the College of Basic Education, 2022)
The issue of metaphor occupied an important aspect of the intellectual effort of the men of language, rhetoric, and origins alike, and before we delve into the detailed aspects related to the truth and metaphor at Allama Al-Hilli and others, we will first present the dispute that took place among Muslims about the origin of the truth of the existence of metaphor in language and in the Holy Qur’an.